Assessment of choroidal vascularity and choriocapillaris blood perfusion in Chinese preschool-age anisometropic hyperopic amblyopia children - Hui, Wang; Xiaofeng, Hu; Hua, Xin; Yihan, Dong; Yong, Tao (Frontiers in Pediatrics, 2022)
Purpose To determine the macular and peripapillary area choroid microstructure parameters of hyperopic anisometropic amblyopia eyes and compare to fellow and age-matched control eyes. To assess the correlation between the axial length (AL), choroidal thickness (CT) and choroid microstructure parameters. Methods This cross-sectional comparative, non-interventional study involved 52 hyperopic anisometropic amblyopia children and 48 age-matched heathy controls. 52 eyes with hyperopic anisometropic amblyopia and 48 age-matched control eyes were studied. The peripapillary and subfoveal CT were determined. The total choroidal area (TCA), luminal area (LA), and stromal area (SA) of the subfoveal and peripapillary choroid were measured. In addition, the correlation between the AL, CT and choroid microstructure parameters were calculated. Results The peripapillary and subfoveal CT of the amblyopic eyes was significantly thicker than the fellow and control eyes (all P < 0.05). The subfoveal and peripapillary choroidal SA, LA and TCA of the amblyopic eyes were significantly increased than that of the fellow and control eyes (all P < 0.05). The choroidal vascularity index (CVI) values of the amblyopic eye were significantly different among the three groups (P < 0.05). There was a statistically significant negative correlation between AL and subfoveal CT (SFCT), LA and TCA levels (P < 0.001, P = 0.039, P = 0.027, respectively). Spherical equivalent (SE) was positive correlated with SFCT, LA and TCA levels (P = 0.456, 0.229 and 0.240, respectively; all P < 0.05). There was a statistically significant positive correlation between SFCT, SE, LA, SA, TCA and CVI levels (all P < 0.05). Conclusion The subfoveal and peripapillary CT of amblyopic children abnormally increased and correlated with shorter AL and higher SE. The choroidal structure of the amblyopic eyes was different from the fellow and control eyes, the hyperopic anisometropic amblyopic eyes had significantly thicker sub-foveal choroid, higher LA, SA, and TCA. AL and CT affect choroidal structure and vascular density. Choroidal blood flow may be increased in amblyopic eyes. The larger LA, SA, TCA, and lower CVI were characteristic of the amblyopic eye.